Activated Ras requires autophagy to maintain oxidative metabolism and tumorigenesis - Guo, Jessie Yanxiang; Chen, Hsin-Yi; Mathew, Robin; Fan, Jing; Strohecker, Anne M.; Karsli-Uzunbas, Gizem; Kamphorst, Jurre J.; Chen, Guanghua; Lemons, Johanna M.S.; Karantza, Vassiliki; Coller, Hilary A.; DiPaola, Robert S.; et al. (Genes & development, 2011)
Autophagy is a catabolic pathway used by cells to support metabolism in response to starvation and to clear damaged proteins and organelles in response to stress. We report here that expression of a H-ras V12 or K-ras V12 oncogene up-regulates basal autophagy, which is required for tumor cell survival in starvation and in tumorigenesis. In Ras-expressing cells, defective autophagosome formation or cargo delivery causes accumulation of abnormal mitochondria and reduced oxygen consumption. Autophagy defects also lead to tricarboxylic acid (TCA) cycle metabolite and energy depletion in starvation. As mitochondria sustain viability of Ras-expressing cells in starvation, autophagy is required to maintain the pool of functional mitochondria necessary to support growth of Ras-driven tumors. Human cancer cell lines bearing activating mutations in Ras commonly have high levels of basal autophagy, and, in a subset of these, down-regulating the expression of essential autophagy proteins impaired cell growth. As cancers with Ras mutations have a poor prognosis, this “autophagy addiction” suggests that targeting autophagy and mitochondrial metabolism are valuable new approaches to treat these aggressive cancers.